Peran Guru PAI Dalam Pembinaan Siswa Terhadap Permasalahan Pergaulan Bebas di SMK N 1 Ampek Angkek - Lubis, Rahmat Machmul; Darti, Yenni; Monia, Fenny Ayu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research is motivated by problems encountered in the field, namely at SMKN 1Â  Ampek Angkek, this type of research is descriptive qualitative research. Based on the results of research in the field, several problems have been found at SMKN 1 Ampek Angkek, where there are still many students there who engage in promiscuity without any filter within themselves, so they fall into things that are prohibited by the Islamic religion and norms. socio-cultural norms. These include students dating, having video call sex (VCS), smoking, getting pregnant out of wedlock, and saving and watching pornographic videos. One of the factors that causes student promiscuity is the influence of social media use. This is of course a very big problem which causes the relationship between fellow students to become bad, therefore the role of Islamic Religious Education teachers is very necessary to overcome this problem, Islamic Religious Education teachers need to fully instill Islamic values in individual students, one of which is by providing good role models to their students.